HEALTH SOCIAL SECURITY REFERRAL SYSTEM IN TOTO KABILA REGIONAL GENERAL HOSPITAL, BONE BOLANGO DISTRICT - Malaha, Adnan; Nurhidayah, Laila (LPPM Universitas Bina Mandiri Gorontalo, 2023)
ABSTRACT This research aims toknow how human resources are at the Toto Kabila Regional General Hospital, the availability of facilities and infrastructure for the implementation of the Health Social Security participant service system and know the Health Social Security verification system that exists at the Toto Kabila Regional General Hospital. The method used in this study is the type of research thatis descriptive- Qualitative with a qualitative approach using data collection methods of observation, interviews and documentation The results of this study were obtained in terms of sufficient human resources and no shortage of health workers, in terms of material (facilities and infrastructure) is not adequate becausethe lack of printing and computer facilities that sometimes have errors and in terms of the verification system already uses a bridging system that is fast and efficient in service. In the registration flow process by the patient, there were no errors during the service process, even so the deficiencies could still be handled properly by the Toto Kabila Hospital, Bone Bolango Regency, so that patients still get a good service process so that the health social security referral system is maximized.